STRENGTHENING COMMITMENT TO ORGANIZATION, ENTREPRENEURSHIP, EMPOWERMENT AND PERSONALITY IN IMPROVING TEACHERS’ INNOVATIVENESS - Uun Nurhayati; Sri Setyaningsih; Widodo Sunaryo (JF Publisher, 2023)
The education in Indonesia requires the development of educational facilitators, including the teachers. Teachers has main role in the preparation of applicable learning materials that can be understand easily by students to develop their character and skills. Therefore, teachers must be highly innovative and able to provide learning equipment that can achieve learning goals. This research aims to obtain strategies and efforts to improve the innovativeness of teachers in Private Vocational High School in Bogor, and to identify the relationship between each variable to improve the innovativeness of a teacher. The research method used in this research is path analysis and SITOREM (Scientific Identification Theory to Conduct Operation Research in Education Management) to examine the direct relationship and indirect relationship between exogenous and endogenous variables. The research findings revealed that there are significant positive direct impact between each variables that need to be maintained to improve the innovativeness of teacher.